Computational Fluid Dynamics and Fluid Flow Visualization Methods (Proceedings of Faculty of Civil Engineering, 2021)
This paper deals with application and purpose of Computational Fluid Dynamics (CFD) in everyday practice and methods of fluid flow visualization. In order to facilitate the understanding of the concept of turbulence model the paper presents the basic characteristics of the fluid, of which the focus is on viscosity and compressibility. For the purpose of describing the dynamics of fluid motion, the basic governing equations of fluid flow are defined, which include laminar and turbulent flow regimes. A significant focus of this paper is given to the creation of numerical models using CFD, from preprocessing, defining the problem domain, creating a numerical network, to necessary parameters for defining individual turbulent models and methods of visualizing the solution of the observed problem through postprocessing. The second part of the paper discusses experimental and computational methods of fluid flow visualization, within which individual examples for each of the visualization methods are given.
Keywords: Computational Fluid Dynamics; viscosity; compressibility; Navier-Stokes equations; numerical modeling; flow visualization methods